Factors Affecting Customer Satisfaction of the Wi-Fi Services (Sains Humanika, 2012)
Measuring the quality of service and customer satisfaction is ultimately important for ISPs to remain in business. In order to achieve a good quality of service, understanding the two-way relationship among customers in a variety of patterns of quality of service is crucial. Three methods of analysis namely; Penalty Rewards Contrast Analysis (PRCA), Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) were used in the analysis to identify the causes of the main problems that affect the level of customer satisfaction. For the PRCA analysis, factors that were categorized as one-dimensional are service quality, promotion, as well as payment of bills of paid Wi-Fi services and the promotional factor of free Wi-Fi services. Based on the IPA results, there were eight attributes for paid Wi-Fi services and four attributes of free Wi-Fi services in the first quadrant. These attributes are important but their performance are low. Therefore, these attributes need to be emphasized further to increase their level of performance. Meanwile, the CSI analysis showed that all five factors are found to be at a good level and being categorized in the indifferent zone.
Keywords: Wi-Fi; customer satisfaction Index; penalty reward contrast analysis; important performance analysis